A survey of oncology advanced practice providers' knowledge and attitudes towards sexual and gender minorities with cancer. Issue 15 (11th May 2020) - Sutter, Megan E.; Bowman‐Curci, Meghan L.; Duarte Arevalo, Luisa F.; Sutton, Steven K.; Quinn, Gwendolyn P.; Schabath, Matthew B.
Abstract: Aims and objectives: To evaluate the knowledge and attitudes towards sexual and gender minority (SGM) oncology patients' needs among advanced practice providers (APPs). Background: SGM individuals experience health disparities, in part due to lack of access to knowledgeable providers. Despite the important role of APPs in cancer care, less is known about their attitudes and knowledge towards SGM cancer patients. Design: Cross‐sectional study. Methods: A survey of APPs at a National Cancer Institute‐Designated Comprehensive Cancer Center assessed self‐reported demographics, attitudes, knowledge and postsurvey confidence in knowledge of SGM oncology patient needs. Reporting of this study adheres to STROBE guidelines. Results: Knowledge of health needs was low with an average of 2.56 ( SD = 1.27) items answered correctly out of 6. The majority of APPs self‐reported being comfortable treating SGM patients (93.6% and 87.2%, respectively), but less confident in knowledge of their health needs (68.0% and 53.8%, respectively). Although less than half of APPs believed education should be mandatory (44.9%), 79.5% were interested in education about SGMs' unique health needs. Political affiliation, medical specialty, licensure, and having SGM friends or family were associated with various attitude items, but not knowledge. Moderation analyses indicated that APPs who had greater overall knowledge scores were more likely to agree, on average, that knowing sexual orientation, gender identity and sex assigned at birth are important to providing quality oncology care. Conclusion: APPs report being comfortable providing care for SGMs with cancer, but knowledge gaps remain that may inhibit the quality of care provided. Given the interest in education, results would support the development of SGM‐related healthcare training for oncology APPs. Relevance to clinical practice: Targeted education for providers during training and continuing education is likely to improve the provision of quality care for SGMs with cancer.